Does Covert Retrieval Benefit Adolescents’ Learning in 8th Grade Science Classes? - Amber E. Witherby; Paige E. Northern; Sarah K. Tauber (Behavioral Sciences, 2025)
Retrieval practice can benefit students’ long-term learning. However, no prior investigations have explored the degree to which response mode—overt versus covert retrieval—moderates the impact of retrieval practice on adolescents’ learning in a classroom context. To explore this issue, 8th grade students learned science concepts that were required for their class. They learned terms in their middle school classrooms by recalling and writing them down (overt retrieval), mentally recalling (covert retrieval), or restudying definitions. They practiced each strategy in 5 sessions and took final tests 2 days later. The impact of covert retrieval on students’ learning was similar to that of restudy, and both covert retrieval and restudy were less beneficial relative to overt retrieval. Treatment package effectiveness differed somewhat between students and terms. These outcomes are generally consistent with the retrieval dynamics hypothesis and reveal that response mode can impact the effectiveness of retrieval practice in middle school classrooms.